Proxy voting in the U.S. House of Representatives: Legislative shirking in new clothing? - Mixon, Franklin G.; Torgler, Benno (Frontiers in Applied Mathematics and Statistics, 2023)
New technological developments have heightened interest in understanding and evaluating new tools of participatory and representative engagement in the political sphere. Recent academic research in this area is mainly theoretical, and focuses on voters rather than legislators. This study addresses this gap in the literature by empirically exploring the unique case of proxy voting by members of the U.S. House of Representatives that was introduced as an emergency measure to allow the Congress to function during COVID-19. The core result from this study, given its finding that voting abstention during 2019 is positively correlated with the use of proxy voting during 2021, indicates that proxy voting in this case is connected to legislative shirking. Thus, it appears that the proxy voting mechanism introduced in 2020 via a U.S. House resolution represents a new configuration of traditional legislative shirking or vote skipping.